Upaya Meningkatkan Reputasi Pondok Pesantren Darul Ilmi Wal Amal Melalui Promosi Online Dan Offline - Neni Sumarni; Netti Nurlenawati; Citra Savitri; Rieke Retnosary (Universitas YARSI, 2025)
This study aims to analyze the implementation of promotional strategies at Pondok Pesantren Darul Ilmi wal Amal to enhance the institution's popularity and reputation. This research employs a qualitative descriptive approach, with data collection methods including observation, interviews, document review, and literature studies. The study subjects consist of the pesantren management, majlis taklim members, and students' parents. The findings reveal that online promotion through social media can increase public curiosity about the pesantren, while offline promotion via events, such as Milad celebrations, is more effective in providing a comprehensive depiction of the pesantren. The popularity indicators, including recognition, appeal, expertise, and characteristics of the pesantren, were successfully improved through promotions. However, reputation indicators such as widespread recognition and ease of remembrance were not fully achieved. The study concludes that a combination of online and offline promotions can complement each other in attracting public interest. The implications highlight the importance of planned promotional management and the involvement of students' parents through testimonials to enhance public trust. Further research is needed to explore more effective promotional strategies for improving institutional reputation